Sustainability and impact assessment of IPM in Basmati rice (Oryza sativa) - SINGH, S; TANWAR, R K; SINGH, S P (The Indian Journal of Agricultural Sciences, 2022)
Integrated pest management (IPM) strategy has greatly contributed to a progressive commitment for sustainable agriculture in India. Long term studies conducted on validation and promotion of IPM in basmati rice (Oryza sativa L.) in district Gautam Budh Nagar, Uttar Pradesh, India resulted in a gradual enhancement in the area under IPM from 40 ha in 2010 by participation of 25 farmers to 990 ha in 2019 by participation of 654 farmers from 42 villages. Implementation of IPM technology resulted in a significant (P<0.05) reduction in the incidence of yellow stem borer (69.64%), leaf folder (70.9%), brown plant hopper (55.52%), bakane (90.98%) and the population of root-knot nematode (76.8%) over farmers’ practices (FP). It enhanced the population of predatory spiders (84.2%), beneficial soil nematodes (159.27%) and bio-agents, viz. Pseudomonas fluorescens (78.74%) and Trichoderma harzianum (81.34%) over FP. Application of chemical pesticides was reduced to 75.25 g/ha in IPM against 892.93 g/ha in farmers’ practice. The maximum residue level of buprofezin, a widely used insecticide, was recorded below detectable level in paddy grains. Long term studies indicated higher yield (38.0 q/ha) as well as benefit:cost ratio (3.6) in IPM as compared to FP yield (30.5 q/ha) and benefit:cost ratio (2.3) with 58.3% enhancement in net return over FP. Thorough analysis of the data indicated the availability of critical inputs, accessibility of farmers to subject matter specialists through Farmer Field Schools and market for IPM produces as the main factors responsible for sustainability and horizontal spread of IPM in Gautam Budh Nagar.